GENERATORS OF BOREL MEASURABLE COMMUTATIVE ALGEBRA ON COMPACT HAUSDORFF TAKING VON NEUMANN AW* OVER *-ISOMORPHISM - Deep Bhattacharjee, (EPRA International Journal of Research and Development (IJRD), 2022)
For any complex valued functions over any topological space there exists a relation in von Neumann algebras of *-graded that is bounded on compact Hausdorff where for category- I, II, III there exists a commutative form of algebras such that to satisfy a monotone complete algebra suffice an isomorphic factor on the same tamed as having the generators for a generic group for 2-groups and for the former being additive integers generating the later free group for algebras where Hausdorff a Borel measure exists in compact set norms the associated Hausdorff space over a locally finite via .